Baobab Leaf Powder Efficacy as Turbid Water Treatment Biocoagulant - Gram, Vahyela; Kasinath, Archana; Abubakar, Abdulhalim Musa; Pandit, Gaurav Kumar; Ngulde, Aliyu Buba; Saka, Tahiru; Mustapha, Zanna (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2024)
The high cost of treated water makes most rural communities resort to readily available sources that are normally of low quality, which exposes them to waterborne diseases in the process. In the present study, various doses of baobab (Adansonia digitata) leaf powder coagulant (i.e., 0.1, 0.2, and 0.3g per 50 mL turbid water) were added to the surface water sample collected. It was found that increasing the coagulant doses results in either a decrease or increase in the measured parameters, such as pH, turbidity, and electrical conductivity (EC). At constant 30 min coagulation time, pH and EC of the turbid water samples taken were within WHO standards. However, the labeled sample fed with 0.3g of baobab leaf powder coagulant gave the lowest turbidity of 78.7 NTU. A reduction in final turbidity is a clear indication of the coagulation capabilities of baobab leave powder. With this study, baobab leave (as a potential coagulant) is a new addition to the literature, apart from its seed and pulp which have been experimented with previously. Natural coagulants contain some chemicals whose effect on the resulting treated water needs to be examined. If need be, an additional treatment unit must be set up to adsorb or remove those contaminants from the water before proper use.